The Sea as a Border, the Sea as an Experience: Artistic Engagements with the European Migration Crisis in Three Films - Angelis,Emma De (2021)
Abstract In recent years, migration has become one of the most important issues in the political and cultural discourse across Europe. Inflows through the Mediterranean Sea, in particular, have reminded the European public of the ambivalent effects of globalization, and of the fragility and the ethical questionableness of how political borders are drawn and geographical boundaries perceived. Artistic engagements with the topic shed light on both collective fears and political responses to global challenges, allowing to deconstruct human institutions, such as borders, that have at present acquired the status of a second nature. The article explores three relevant case studies, and attempts to clarify how artistic forms of communication vehiculate ethical insights by aesthetic means, allowing the European audience to gain an outer perspective on ingrained cultural and political practices.